Prognostic value of N-terminal pro-brain natriuretic peptide in elderly people with acute myocardial infarction: prospective observational study. (6th May 2009) - Lorgis, L; Zeller, M; Dentan, G; Sicard, P; Buffet, P; L'Huillier, I; Beer, J C; Vincent-Martin, M; Makki, H; Gambert, P; Cottin, Y
Abstract : Objective To examine the influence of age on the predictive value of N-terminal pro-brain natriuretic (NT-proBNP) peptide assay in acute myocardial infarction. Design Prospective observational study. Setting All intensive care units in one French region. Participants 3291 consecutive patients admitted for an acute myocardial infarction, from the RICO survey (a French regional survey for acute myocardial infarction). Main outcome measure Cardiovascular death at 1 year. Results Among the 3291 participants, mean age was 68 (SD 14) years and 2356 (72%) were men. In the study population, the median NT-proBNP concentration was 1053 (interquartile range 300-3472) pg/ml. Median values for age quarters 1 to 4 were 367 (119-1050), 696 (201-1950), 1536 (534-4146), and 3774 (1168-9724) pg/ml (P<0.001). A multiple linear regression analysis was done to determine the factors associated with the pro-peptide concentrations in the overall population. NT-proBNP was mainly associated with age, left ventricular ejection fraction, creatinine clearance, female sex, hypertension, diabetes, and anterior wall infarction. At one year's follow-up, 384 (12%) patients had died from all causes and 372 (11%) from cardiovascular causes. In multivariate analysis, NT-proBNP remained strongly associated with the outcome, beyond traditional risk factors including creatinine clearance and left ventricular ejection fraction, in each age group except in the youngest one (<54 years) (P=0.29). The addition of NT-proBNP significantly improved the performance of the statistical model in the overall study population (−2log likelihood 3179.58 v 3099.74, P<0.001) and in each age quarter including the upper one (1523.52 v 1495.01, P<0.001).The independent discriminative value of NT-proBNP compared with the GRACE score was tested by a diagonal stratification using the median value of the GRACE score and NT-proBNP in older patients (upper quarter). Such stratification strikingly identified a high risk group—patients from the higher NT-proBNP group and with a high risk score—characterised by a risk of death of almost 50% at one year. Conclusions In this large contemporary non-selected cohort of patients with myocardial infarction, NT-proBNP concentration had incremental prognostic value even in the oldest patients, above and beyond the GRACE risk score and traditional biomarkers after acute myocardial infarction. These data further support the potential interest of clinical trials specifically assessing NT-proBNP measurement as a guide to current treatment strategies, as well as novel strategies, in older patients with acute myocardial infarction.